Elderly in Lithuanian Media: Naive, Suffering and Helpless - Rapolienė, Gražina (Sociologija. Mintis ir veiksmas, 2010)
The world shaped by the media is taken over by its audience. The media homogenizes different views, influences age identity of individuals and attitudes towards their own and other age groups. Western research reports under-representation of elderly, especially women, and they are often portrayed negatively in physical, psychological and social sense. In this paper images of elderly in 396 publications of 2007 on the internet portal Delfi are analyzed. Contrary to the Western trends, elderly women here are more often represented than men. Dominating criminal reports, as previously, create the image of victims – weak, naive, harmed elderly, accentuated by the trends of old age institutionalization. Positive pole in the Lithuanian media is represented by the image of fighters, public figures, deportees (instead of Western healthy leisure class representative image).